Ridge Preservation Procedures after Tooth Extractions: A Systematic Review - Gabriella Balli; Andreas Ioannou; Charles A. Powell; Nikola Angelov; Georgios E. Romanos; Nikolaos Soldatos (International Journal of Dentistry)
Background. The purpose of this systematic review was to accurately assess the procedural success of ridge preservation technique through the application of strict inclusion and exclusion criteria. Data Sources. A methodical search of PubMed of the US National Library of Medicine and the Cochrane Central Register of Controlled Trials was conducted for applicable articles. Only randomized controlled trials comparing ridge preservation treatment with a nongrafting control, ten-subject minimum sample size, and three or more months of follow-up were included in our study. Types of Studies Reviewed. In a screening between January 1980 and September 2017, articles meeting predetermined criteria were further examined in a qualitative data analysis. A thorough search of the databases provided 1876 articles. Of these records, 174 were assessed for eligibility through the systematic employment of inclusion and exclusion criteria. Results. Two records were appropriate for further data analysis. One study used a mixture of a deproteinized cancellous bovine bone and porcine collagen fibers in a block form (DBB/CF), while the other study used leukocyte-platelet-rich fibrin (L-PRF). The use of DBB/CF reduced the magnitude of vertical bone resorption, yet the study showed high risk of bias. The use of L-PRF reduced the magnitude of both the horizontal and vertical crestal bone resorption; however, the low sample size created wide standard deviations between the test and control groups. Inherent weaknesses were present in both studies. Through methodical analysis of both records, the dissimilarities prevented the conduction of a meta-analysis. Implications of Key Findings. Within the limitations of this systematic review, L-PRF reduced the magnitude of vertical and horizontal bone resorption, which places L-PRF as a potential material of choice for ridge preservation procedures. Conclusions. Within the limitations and weaknesses of both studies, the use of DBB/CF prevented the vertical crestal bone resorption while the L-PRF prevented both the horizontal and vertical crestal bone resorption. More randomized controlled clinical trials are needed to eliminate all the confounding factors, which bias the outcome of ridge preservation techniques.